2017
DOI: 10.1002/jcb.25935
|View full text |Cite
|
Sign up to set email alerts
|

The Role of c‐SKI in Regulation of TGFβ‐Induced Human Cardiac Fibroblast Proliferation and ECM Protein Expression

Abstract: Cardiac fibrosis is characterized by over-deposition of extracellular matrix (ECM) proteins and over-proliferation of cardiac fibroblast, and contributes to both systolic and diastolic dysfunction in many cardiac pathophysiologic conditions. Transforming growth factor β 1 (TGFβ1) is as an essential inducing factor of cardiac fibrosis. C-Ski protein has been identified as an inhibitory regulator of TGFβ signaling. In the present study, we revealed the repressive effect of c-Ski on TGFβ1-induced human cardiac fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…TGF-β induces cellular matrix production by activating MFB during cardiac fibrogenesis; however, transient Ski overexpression in MFB decreases Smad2 phosphorylation, which results in a decrease in type I collagen synthesis and α-SMA levels. 169 , 240 In this case, stable overexpression of Ski promotes cardiac MFB apoptosis. 241 Bone marrow progenitor cell therapy modulates cardiac fibrosis in diabetic hearts by decreasing miR-155 levels, whereas overexpression of miR-155 in cardiac fibroblasts inhibits Ski and SnoN expression.…”
Section: Regulation Of Tgf-β/smad Signaling By Ski and Snonmentioning
confidence: 99%
“…TGF-β induces cellular matrix production by activating MFB during cardiac fibrogenesis; however, transient Ski overexpression in MFB decreases Smad2 phosphorylation, which results in a decrease in type I collagen synthesis and α-SMA levels. 169 , 240 In this case, stable overexpression of Ski promotes cardiac MFB apoptosis. 241 Bone marrow progenitor cell therapy modulates cardiac fibrosis in diabetic hearts by decreasing miR-155 levels, whereas overexpression of miR-155 in cardiac fibroblasts inhibits Ski and SnoN expression.…”
Section: Regulation Of Tgf-β/smad Signaling By Ski and Snonmentioning
confidence: 99%
“…[17][18][19] Recently, researchers have focused on the effects of c-Ski in cardiac fibrosis. 13 Experimental studies in animal models revealed that atrial fibrosis plays an important role in the induction and maintenance of AF. 20 Zhang et al found that c-Ski can ameliorate isoproterenol-induced myocardial fibrosis in a rat model and reduce both TGF-β1-induced proliferation of primary rat cardiac fibroblasts and ECM deposition.…”
Section: Discussionmentioning
confidence: 99%
“…10 Cunnington et al demonstrated the antifibrotic properties of c-Ski and its role in the regulation of cardiac myofibroblast phenotype and contractility. 13 Although these studies provided promising evidence in support of the involvement of c-Ski in cardiac fibrosis, mechanistic data on the roles of these small molecules in AF and the associated atrial remodelling in animal models are still lacking. 12 In addition, our previous studies confirmed the repressive effect of c-Ski on TGF-β1-induced human cardiac fibroblast proliferation and ECM protein synthesis.…”
mentioning
confidence: 99%
“…However, no precise mechanism underlying the pathogenic process of cardiomyocyte hypertrophy had been reported. Currently, metalloproteinase and integrin in extracellular matrix are considered to be the major factors related with cardiac remodeling 11. Integrins usually act as mediator and mechanical pressure transmitters between cells and extracellular matrix, activate the integrin signaling pathway, and then affect various cellular functions 12, 13…”
Section: Introductionmentioning
confidence: 99%
“…Currently, metalloproteinase and integrin in extracellular matrix are considered to be the major factors related with cardiac remodeling. 11 Integrins usually act as mediator and mechanical pressure transmitters between cells and extracellular matrix, activate the integrin signaling pathway, and then affect various cellular functions. 12,13 A disintegrin and metalloprotease-22 (ADAM22) is a member of the ADAM family, which is transmembrane and secreted metalloendopeptidases that can regulate cell adhesion, inflammation, and cancer development.…”
mentioning
confidence: 99%